Keterlibatan Orang Tua dalam Mewujudkan Pendidikan Anak Usia Dini Ramah Anak di Gugus Budi Mulia II Sukoharjo - Pudyaningtyas, Adriani Rahma; Rahmawati, Anayanti; Hafidah, Ruli; Palupi, Warananingtyas; Dewi, Nurul Kusuma; Sholeha, Vera; Syamsuddin, Muhammad Munif (DEDIKASI: Community Service Reports, 2023)
Child-Friendly Schools (SRA) prioritize children's rights in learning to actualize individuals who need to be educated with good treatment. The SRA concept is intended to create a safe and enjoyable learning atmosphere at all levels of education, including early childhood education. A comfortable learning atmosphere for students positively impacts physical and psychological well-being, which leads to optimal developmental tasks. There are six components in the implementation of child-friendly PAUD, namely 1)policy, 2)curriculum implementation, 3)educators and education staff, 4)infrastructure, 5)child participation, and 6)parent and community participation. The group needs help realizing child-friendly PAUD, one of which is that the activity programs carried out by these PAUD institutions must meet the SRA indicators. The activity program in question is more specifically an effort to involve parents in realizing SRA. Parenting activities that have been carried out so far have yet to be in harmony with the activities carried out by schools, especially in fulfilling children's rights. Therefore it takes school principals' and teachers' knowledge and skills to design parenting activity programs aligned with school activities to realize SRA. This community service aims to carry out training in preparing parenting activity programs. The method for implementing this activity program consists of five stages, namely: 1)analysis of problems in partner institutions; 2)socialization (brainstorming and equalization of perceptions); 3)workshops; 4)assisting the implementation of child-friendly PAUD activity programs; 5)evaluation.